العلم االلهي بالجزئيات: مقاربة ابن سينا وصدر المتألهين نموذجا - السيد خالد سيساوي خمينى (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
The philosophical problems have closed ties with the principle of tawhid. One of them is the problem of ‘divine knowledge’ about the particular matters. This article shows those problems from the approach of Ibn Sīna and Mulla Ṣadra. Ibn Sīna holds that the Divine Essence knows the particular things in a universal form rather than in a particular. That is to say in the form of causality of forms that manifested in the system of existence (wujūd). Mulla Ṣadra on the other hand agrees that the Divine Essence is the forms of everything, without exception. He interprets the knowledge of God to the particular things that exist in the matter without any changing in the Divine knowledge itself, along with the events that turn.